1996
DOI: 10.1053/jhep.1996.v24.pm0008855195
|View full text |Cite
|
Sign up to set email alerts
|

Progressive decrease in tissue glycogen content in rats with long-term cholestasis

Abstract: show a reduction in nonoxidative glucose metabolism, 3,4 findLiver and skeletal muscle glycogen metabolism were ings compatible with impaired glycogen synthesis. 5 In supinvestigated in rats 1 and 4 weeks after bile duct ligation port of this concept, glycogen synthase activity has been (BDL) and in pair-fed, sham-operated control rats. Livfound to be reduced in skeletal muscle from cirrhotic paers were subjected to morphometric analysis to express tients. 5 Similarly, in rats with carbon tetrachloride (CCl 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…These changes do not seem to be progressive as there are not differences between rats 17 and 31 days after BDL. These observations are in agreement with those of several authors (Muriel et al, 1994;Krähenbühl et al, 1996). These animals also show portal hypertension that we determine indirectly through increase of splenic pressure and weight.…”
Section: Discussionsupporting
confidence: 94%
“…These changes do not seem to be progressive as there are not differences between rats 17 and 31 days after BDL. These observations are in agreement with those of several authors (Muriel et al, 1994;Krähenbühl et al, 1996). These animals also show portal hypertension that we determine indirectly through increase of splenic pressure and weight.…”
Section: Discussionsupporting
confidence: 94%
“…Glucagon as well as catecholamines (noradrenalin and adrenalin) are known to trigger glycogenolysis via activation of phosphorylase A and to decrease glycogen synthesis by inhibiting glycogen synthase, leading to a reduction of the hepatic glycogen stores [5]. In a previous study, we showed that the plasma levels of glucagon and catecholamines increase after laparotomy [26,27,30]. The observed decrease in the hepatic glycogen stores after laparotomy is therefore most likely the consequence of a more accentuated stress response in comparison to laparoscopy.…”
Section: Discussionmentioning
confidence: 88%
“…A decrease in the hepatic glycogen content has been shown to be associated with impaired glycogenolysis in perfused rat livers [26] and could therefore lead to reduced plasma glucose concentrations. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to hepatic fibrosis, chronic biliary obstruction results in deranged hepatic energy metabolism and increased oxidative stress [42,43]. Among the adaptive responses was an activation of the pentose phosphate pathway and up-regulation of the anti-oxidant glutathione S-transferase.…”
Section: Discussionmentioning
confidence: 99%